TEACHING ENGLISH LISTENING COMPREHENSION USING THE FLIPPED INSTRUCTION MODEL - Nindi Rika Riani; Nurdin Noni; Sukardi Weda; Muh Tahir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study investigated the effectiveness of the flipped learning model in teaching listening comprehension to students. Using a quasi-experimental design, 48 students were divided into an experimental group, which received flipped learning, and a control group, which received conventional learning. Pre-test and post-test assessments measured listening comprehension achievement, while questionnaires explored students’ perceptions and difficulties with the flipped learning model. Statistical analysis revealed no significant difference in pre-test scores between the groups, confirming initial equivalence. However, post-test results showed significant improvement in the experimental group compared to the control group, with a large effect size (Cohen’s d > 1.5. In addition, all students in the experimental group exceeded the minimum mastery criterion. Questionnaire data showed that students perceived the flipped classroom positively and reported minimal difficulties in adapting to the model. These findings suggest that flipped learning not only improves listening comprehension outcomes but also promotes greater student engagement and autonomy. This study supports the integration of the flipped classroom as an effective pedagogical approach in language education.